Exploring Service Innovation in Cultural and Creative Blocks from the Perspective of Value Resonance - Shih-Ling Kuo; Chun-Liang Chen (SAGE Open)
The revitalization of cultural and creative blocks is seen as an important economic strategy for stimulating local industries; driving local economic development; creating employment opportunities; attracting entrepreneurs, tourists and residents; and developing the city as a whole in city marketing cases. This study uses exploratory research as a research strategy to examine how actors in cultural and creative blocks achieve service innovation in those blocks through value co-creation based on value resonance. Through the integration of resources, actors propose shared values and exchange services through service systems. In the process of exchanging services, the actors integrate their values, co-establish institutional arrangements, and create value resonance. Under the premise of value resonance, they then co-create value and achieve service innovation in cultural and creative blocks. This study explores the original functions of cultural and creative blocks, such as cultural preservation, enhancing a city’s image and serving as a tourist attraction, and analyses the value-enhancing and innovative services of these places, which will help to examine the effectiveness of the revitalization of cultural and creative blocks and the operations of innovation activities. Furthermore, this study put forward suggestions for the development of the cultural and creative block industry from the aspects of policy, economy, and society to provides innovative ways of thinking about the sustainable development of cultural and creative blocks and the invigoration of local economies.